Evaluation of the efficacy of neonicotinoid and pyrethroid insecticides in Diaphorina citri Kuwayama (Hemiptera: Liviidae) populations in Colombia - Ramírez Godoy, Augusto; Puentes Pérez, Gina; Restrepo Díaz, Hermann (Universidad Pedagógica y Tecnológica de Colombia, 2019)
1 recurso en línea (páginas 358-368).